The orthodox tradition of intercession (Pechalovanie) in the supramoralistic projection of the philosophy of the common cause (N. F. Fedorov) - Onosov, Alexander (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. I, Bogoslovie, filosofii͡a, 2024)
The main goal of the work is an analytical study of the category “sadness” as one of the important ones in the philosophy of the common cause N.F. Fedorov (1829–1903). It is noted that sadness in supramoralism acquires the status of a special concept that expresses the socio-religious perception of the “non-peaceful” state of the world. Sadness is expressed by a rationally conscious and emotional-sensual experience of the phenomena of socio-natural unrelatedness; regret about the immaturity of humanity, about the moral and physical incompleteness, sinfulness and mortality of man. In Christianity sadness acquired a moral depth and hope for deliverance from unrelatedness and discord. Using the method of content analysis, the peculiarities of understanding the moral phenomenon of sadness in Orthodoxy are revealed, a brief excursion into the history of the Orthodox tradition of sadness is taken, and the modern content of sadness as a concept and as a special duty of the patriarch of the Russian Church is revealed. Supramoralism considers the only possible solution to this question the complete reconciliation of churches in a holistic and active Christian doctrine based on Orthodoxy, which is precisely sadness about the division of Christianity into separate branches. The article reveals an important semantic point of Fedorov’s teaching — the interpretation of the threat of the Apocalypse as a conditional prophecy requiring a morally active warning by humanity itself. It is concluded that in supramoralism sadness means the acceptance and fulfillment by humanity, which has come to the mind of truth, to duty of ontological transformation of the world. In its active function sadness is carried out as a general service of natural regulation. The result of the study is the explication of the deep active-christian meaning of sadness. In the supramoralistic understanding sadness expresses the principle of conscious and active participation of humanity in the world ontology, which opens up the possibility of a systematic solution to the fundamental issues of the existence of planetary society for a distant and good future.